(untitled) (World Bulletin of Public Health, 2023)
Gout is a rheumatic disease characterized by hyperuricemia. It causes recurrent attacks of inflammation, pain, disability, and discomfort due to the accumulation of urate crystals in the joints, caused by overproduction or underexcretion of uric acid. Recent studies have shown that gout patients are prone to cardiovascular disease, including coagulation disorders like PE and DVT. The paper aims to summarize the possible link between gout and coagulation disorders by studying the molecular and genetic features of gout patients